1975
DOI: 10.1093/ajcp/63.4.483
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Hartmannellid Amebic Meningoencephalitis in Zambia

Abstract: A case of amebic meningoencephalitis recognized in an adult Zambian is described. This is the first authenticated case from Africa. The morphologic features of the organism, its ability to form cysts in tissue, and the granulomatous tissue response denote that the ameba is an hartmannellid rather than a Naegleria. Free-living amebas of the family Hartmannellidae have not been incriminated before as a cause of primary amebic meningoencephalitis in man. To our knowledge this is the only case where such an ameba … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Predisposing factors include alcoholism, drug abuse, steroid treatment, cancer chemotherapy, radiotherapy, and organ transplantation (14,282,408). Although enhanced susceptibility to infection is associated with immune suppression and debilitating conditions, cases of GAE caused by Acanthamoeba have been found in immunocompetent children and adults (35,336,368,388,419). The route of infection is thought to be by inhalation of amebae through the nasal passages and lungs or introduction through skin lesions.…”
Section: Granulomatous Amebic Encephalitismentioning
confidence: 99%
See 1 more Smart Citation
“…Predisposing factors include alcoholism, drug abuse, steroid treatment, cancer chemotherapy, radiotherapy, and organ transplantation (14,282,408). Although enhanced susceptibility to infection is associated with immune suppression and debilitating conditions, cases of GAE caused by Acanthamoeba have been found in immunocompetent children and adults (35,336,368,388,419). The route of infection is thought to be by inhalation of amebae through the nasal passages and lungs or introduction through skin lesions.…”
Section: Granulomatous Amebic Encephalitismentioning
confidence: 99%
“…These observations of experimental animals dying from encephalitis led Culbertson et al (99) to predict a role for free-living amebae as agents of human disease. Human cases of amebic encephalitis were reported soon thereafter from Australia, Europe, Africa, South America, and the United States (35,57,58,64,74,142,201,280,284,344,476). However, some of these cases were identified later as primary amebic meningoencephalitis, a rapidly fatal disease of the CNS caused by another free-living ameba, Naegleria fowleri (57,268,286).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] Furthermore, only three clinical related studies regarding Acanthamoeba genus have been reported in Africa: one case of encephalitis due to Acanthamoeba in Dakar, Senegal, 14 an epidemiological study to determine the presence of FLA in the nasal passages of a population in Zaria, Nigeria 24 and the report of three cases of AK in patients from Tunisia. 16 Another case of encephalitis due to a hartmannellid amoeba was reported in Zambia; 25 however, it is possible that the identification of this strain was not carried out correctly. Finally, one sample was positive for B. mandrillaris.…”
Section: Resultsmentioning
confidence: 99%
“…I4 -ltf This seasonal incidence is found in all other PAME cases reported where climatic data is made available. 4 -51 "-12 -1 "- 19 This strongly indicates that warm temperatures are a predisposing factor to the occurrence of PAME. 1K Analysis of the geographical distribution of PAME cases shows that the United States, Australia, Czechoslovakia, and Belgium account for the vast majority of PAME cases.…”
Section: Epidemiology Of Pamementioning
confidence: 93%